2019
DOI: 10.3389/fphys.2019.00485
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependence of Flow Homeostasis in the Left Ventricle

Abstract: Background: Intracardiac flow homeostasis requires avoiding blood stasis and platelet activation during its transit through the cardiac chambers. However, the foundations of intraventricular blood washout and its exposure to shear stresses have been poorly addressed. We aimed to characterize and quantify these features in a wide population of healthy subjects and assess the relationships of these indices with age. Methods: We used color-Doppler echocardiography and custom pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
0
24
1
Order By: Relevance
“…Our observations in the LAA contrast with the finding that considering the kinetics of rouleaux formation notably decreased shear-thinning effects in abdominal aortic and intracranial aneurysms [23]. We attribute this difference to the fact that blood residence time inside the LAA seems to be considerably longer than in aneurysms [23,59] [61], and these features are exacerbated after acute myocardial infarction [12]. Overall, the existing data suggest that non-Newtonian effects in the LV might be appreciable in some pathological conditions.…”
Section: 2contrasting
confidence: 95%
See 2 more Smart Citations
“…Our observations in the LAA contrast with the finding that considering the kinetics of rouleaux formation notably decreased shear-thinning effects in abdominal aortic and intracranial aneurysms [23]. We attribute this difference to the fact that blood residence time inside the LAA seems to be considerably longer than in aneurysms [23,59] [61], and these features are exacerbated after acute myocardial infarction [12]. Overall, the existing data suggest that non-Newtonian effects in the LV might be appreciable in some pathological conditions.…”
Section: 2contrasting
confidence: 95%
“…In the LV, clinical observation of echocardiographic "smoke" suggest RBC aggregates can form in this chamber [81,82] [84], and these features are exacerbated after acute myocardial infarction [13]. Thus, the existing data suggest that non-Newtonian effects in the LV should not be discarded altogether.…”
Section: Effects Of Non-newtonian Rheology On La and Laa Hemodynamics And Blood Residence Timementioning
confidence: 99%
See 1 more Smart Citation
“…19 The apical site of thrombi was explained by Benito who reported that the apex of the ventricle is the most prone to blood stasis. 20 In this study, 80% of the patients with low EF were khat chewers and 80% of LV thrombus were in IHD. This result is consistent with Al-Motarreb et al, who reported that khat chewing is a risk factor for acute MI by causing coronary spasm.…”
Section: Discussionmentioning
confidence: 58%
“…Acquiring a full-field Eulerian velocity field allows for calculation of many relevant parameters, such as vorticity [22], [34], [39], [40], kinetic energy (dissipation) [7], and relative pressure gradients [41]. It is also possible to perform particle displacement analyses using these flow fields to simulate parameters such as particle residence time and washout period [42], [43]. The potential of using echoPIV for assessment of these parameters should be studied and validated in future work.…”
Section: E Future Improvementsmentioning
confidence: 99%